2014
DOI: 10.1007/s11912-013-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Counseling the Patient with Potentially HPV-Related Newly Diagnosed Head and Neck Cancer

Abstract: The recent emergence of a clinically distinct subset of head and neck cancers (HNC) caused by infection with the human papillomavirus (HPV) necessitates critical reevaluation of the existing counseling paradigm for patients with newly diagnosed HNC. Herein we propose a structural framework for patient counseling in which HPV testing is incorporated and the impact of HPV-status is discussed in the context of multiple medical and psychosocial domains. We strive to maintain a balance between making recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Women have felt stigma, anxiety, concern about their relationships and worry about disclosure of their test results to others, following a diagnosis of HPV in the context of cervical screening [24] . As the link between HPV and HNC has been established, there has been increasing recognition of the need for guidance on how to discuss HPV with patients [25] , [26] , [27] . Behavioural and psychological science has made a significant contribution to understanding and addressing psychosocial issues associated with both HNC and HPV.…”
Section: Introductionmentioning
confidence: 99%
“…Women have felt stigma, anxiety, concern about their relationships and worry about disclosure of their test results to others, following a diagnosis of HPV in the context of cervical screening [24] . As the link between HPV and HNC has been established, there has been increasing recognition of the need for guidance on how to discuss HPV with patients [25] , [26] , [27] . Behavioural and psychological science has made a significant contribution to understanding and addressing psychosocial issues associated with both HNC and HPV.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prognostic value of prevalent or persistent HPV detection in oral rinses in predicting risk for OSCC is entirely unknown. It has been suggested that partners of HPV-OSCC patients may be reassured by routine oral cavity and oropharynx screening [123], but there is no evidence to support this recommendation. Indeed, the US Preventive Services Task Force issued a statement in 2013 describing inadequate evidence to recommend screening for oral cancer [124].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Health professionals must be prepared to discuss HPV status because affected patients may want to know the cause of their condition and may question the implications for their sexual partners. 10 11 Although discussions about HPV between patients and health professionals are becoming more common in cervical disease, patients express concern about the stigma attached to sexual transmission. 12–14 There is little rigorous research into how clinicians communicate with patients for the other cancers associated with HPV.…”
Section: Introductionmentioning
confidence: 99%